Bi‐allelic alterations in DNA repair genes underpin homologous recombination DNA repair defects in breast cancer. Issue 2 (27th April 2017) - Mutter, Robert W; Riaz, Nadeem; Ng, Charlotte KY; Delsite, Rob; Piscuoglio, Salvatore; Edelweiss, Marcia; Martelotto, Luciano G; Sakr, Rita A; King, Tari A; Giri, Dilip D; Drobnjak, Maria; Brogi, Edi; et al.
Abstract: Homologous recombination (HR) DNA repair‐deficient (HRD) breast cancers have been shown to be sensitive to DNA repair targeted therapies. Burgeoning evidence suggests that sporadic breast cancers, lacking germline BRCA1 / BRCA2 mutations, may also be HRD. We developed a functional ex vivo RAD51‐based test to identify HRD primary breast cancers. An integrated approach examining methylation, gene expression, and whole‐exome sequencing was employed to ascertain the aetiology of HRD. Functional HRD breast cancers displayed genomic features of lack of competent HR, including large‐scale state transitions and specific mutational signatures. Somatic and/or germline genetic alterations resulting in bi‐allelic loss‐of‐function of HR genes underpinned functional HRD in 89% of cases, and were observed in only one of the 15 HR‐proficient samples tested. These findings indicate the importance of a comprehensive genetic assessment of bi‐allelic alterations in the HR pathway to deliver a precision medicine‐based approach to select patients for therapies targeting tumour‐specific DNA repair defects. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.